1986
DOI: 10.1079/bjn19860089
|View full text |Cite
|
Sign up to set email alerts
|

Perrcentage body fat and prevalence of obesity in a UK offshore population

Abstract: 1. Body-weight, body height and skinfold measurements were taken in 419 adult males working in the UK offshsore oil industry. Percentage body fat was estimated from skinfold thicknesses and the Quetelet index (weight: height2) determined.2. The prevalence of overweightness, assessed from the Quetelet index, in the age groups 20-29,30-39 and 4 W 9 years was 31.6, 50.0 and 66.2% respectively. The Office of Population Census and Surveys (1981) showed that for age-matched groups, the incidence of overweightness i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 8 publications
2
17
0
Order By: Relevance
“…(29). However, these authors included only the linear regression term, whereas the present regression analysis had significant linear (P<0.001) and quadratic (P<0.025) components.…”
Section: Mean Body Mass Indexmentioning
confidence: 96%
“…(29). However, these authors included only the linear regression term, whereas the present regression analysis had significant linear (P<0.001) and quadratic (P<0.025) components.…”
Section: Mean Body Mass Indexmentioning
confidence: 96%
“…In relation to dimensional changes in the offshore workers observed since the 1980s, this observation concurs with the greatest increases in girth occurring at the abdomen and neck, sites renowned for adipose tissue accumulation. While it had previously been observed that offshore workers were 3% heavier and fatter than UK onshore counterparts (Light & Gibson, 1986), because the weight discrepancy has trebled since then, it is reasonable to conclude that fatness will have increased commensurately.…”
Section: Methodsmentioning
confidence: 99%
“…In the 1980s, UK offshore workers were observed to be heavier than age-equivalent by between UK reference males by between 1.5 and 4.6% and had higher estimated body fat than an equivalent aged onshore sample (Light and Gibson, 1986). The average UK offshore worker body weight between 1985 and 2009 rose by 19% to 90.9 kg, approximately 9% heavier than the UK male adult average.…”
Section: Introductionmentioning
confidence: 98%